1990
DOI: 10.1159/000267037
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Blood Flow and Vascular Permeability in Endotoxin-Induced Inflammation

Abstract: Blood flow was measured in several tissues of the rabbit eye following intravitreal injection of a dose of endotoxin that induces an inflammatory response. In separate experiments, the vascular permeability of the inflamed eye was estimated by iris fluorescein angiography and by measuring protein influx into the aqueous humor. The effect of topical corticosteroid treatment upon blood flow and vascular permeability was also measured. Following intravitreal endotoxin injection, minor changes in blood flow occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…The interior of the eye is an immune privileged area. Far lower amounts of complement proteins are found inside the eye, even when the eye is inflamed due to infection [39,40]. Also, membrane-bound regulatory proteins in the eye block deposition of C3b (deposition involved in opsonophagocytosis of gram-positive bacteria) so that the complement pathway will not destroy self-tissue of the eye.…”
Section: Discussionmentioning
confidence: 99%
“…The interior of the eye is an immune privileged area. Far lower amounts of complement proteins are found inside the eye, even when the eye is inflamed due to infection [39,40]. Also, membrane-bound regulatory proteins in the eye block deposition of C3b (deposition involved in opsonophagocytosis of gram-positive bacteria) so that the complement pathway will not destroy self-tissue of the eye.…”
Section: Discussionmentioning
confidence: 99%
“…However, expression levels of TNF-α, IL-1beta, PG2, and MPO were measured in iris and ciliary body samples. Previously, Green et al (4) observed transient elevations in iris, ciliary body, and choroidal blood flow using fluorescein angiography in rabbits with endotoxin-induced experimental uveitis.…”
Section: Discussionmentioning
confidence: 98%
“…LPS injection has been demonstrated to be valid as an experimental model of uveitis and can be performed via intraperitoneal, subcutaneous, intracameral, and intravitreal routes (4,5) . The intravitreal route (26) was chosen in the present study as numerous ocular alterations related to other methods have been reported in previus studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…dotoxin triggers a multitude of potential contributors to inflammation. For example, endotoxin increases vascular permeability (Green et al 1990), stimulates cells to synthesize and release prostaglandins (Bhattacherje 1980), activates the immune response characterized by cytokine release and an intense leukocyte infiltration (Hoekzema et al 1990;Cybulsky et al 1988). To my knowledge, nothing is reported about bilateral effects of unilaterally injected endotoxins.…”
mentioning
confidence: 99%